(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The aim of this study is to look into deforestation processes from the moment that the railway arrived to Michoacán and during the Porfirio Díaz era. In addition, it seeks to analyze the commercialization process of forestry products supplying railway companies, which needed great amounts of wood in order to lay down the rails. The railway boosted possibilities of integrating various commercial regions. However, this progress also meant a certain amount of harm to the forests of Michoacán for the sake of the development that the country was experiencing.